The Contribution of Additional Sampling in Cholecystectomy Materials: A Multicenter Prospective Study - ÇELİKEL, ÇİĞDEM; ERBARUT SEVEN, İPEK (FEDERATION TURKISH PATHOLOGY SOC, 2020)
Objective: Cholecystectomy materials arc frequently encountered in routine practice. The aim of this study was to determine the true frequency of gallbladder lesions, the diagnostic consistency, and standardization of reports after macroscopic sampling and microscopic evaluation based on previously defined criteria. Material and Method: 14 institutions participated in the study within the Hepato-Pancreato-Biliary Pathology Study Group. Routinely examined cholecystectomies within the last year were included in the study in these institutions. Additional sampling was performed according to the indications and criteria. The number of blocks and samples taken in the first macroscopic examination and the number of blocks and samples taken in the additional sampling were determined and the rate of diagnostic contribution of the additional examination was determined. Results: A total of 5,244 cholecystectomy materials from 14 institutions were included in the study. Additional sampling was found to be necessary in 576 cases (10.98%) from all institutions. In the first macroscopic sampling, the mean of the numbers of samples was approximately 4 and the number of blocks was 2. The mean of the numbers of additional samples and blocks was approximately 8 and 4, respectively. The diagnosis was changed in 144 of the 576 new sampled cases while the remaining 432 stayed unaltered. Conclusion: In this study, it was observed that new sampling after the first microscopic examination of cholecystectomy materials contributed to the diagnosis. It was also shown that the necessity of having standard criteria for macroscopic and microscopic examination plays an important role in making the correct diagnosis.
Keywords: Gallbladder; Cholecystectomy; Dysplasia; Cancer; Macroscopy; GALLBLADDER CANCER; LAPAROSCOPIC CHOLECYSTECTOMY; DYSPLASIA; DIAGNOSIS